2019
DOI: 10.1088/1742-6596/1179/1/012167
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity Test of Mangosteen Leaves Ethanol Extract (Garcinia mangostana Linn) Against Pseudomonas aeruginosa Bacteria

Abstract: Pseudomonas aeruginosa causes various infections such as skin infections. Mangosteen leaves contains active compounds that are useful in inhibiting bacterial growth. The purpose of this research is to examine the antibacterial activity of mangosteen leaves ethanol extract (Garcinia mangostana Linn) on the growth of Ps. aeruginosa bacteria. The experiment was conducted by an experimental method of Ps. aeruginosa bacteria using the Kirby-Bauer method. The concentration of ethanol extract from mangosteen leaves s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Mangosteen rind extract has an antibacterial activity which is similar to the research conducted by Suhartati et al 16 , which is suggested that the antibacterial effect of mangosteen rind extract is having a difference on the gram-negative and anaerobic bacteria. Phytochemical screening test of mangosteen rind showed that the ethanol extract of mangosteen rind contained active compounds, such as chrysanthemin, garcinone A, B, and C, sesquiterpenoids, gartanin, fructose, sucrose, tannins, and xanthone as the main content of mangosteen rind.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Mangosteen rind extract has an antibacterial activity which is similar to the research conducted by Suhartati et al 16 , which is suggested that the antibacterial effect of mangosteen rind extract is having a difference on the gram-negative and anaerobic bacteria. Phytochemical screening test of mangosteen rind showed that the ethanol extract of mangosteen rind contained active compounds, such as chrysanthemin, garcinone A, B, and C, sesquiterpenoids, gartanin, fructose, sucrose, tannins, and xanthone as the main content of mangosteen rind.…”
Section: Discussionsupporting
confidence: 86%
“…Permeability disruption of bacterial cells causes their growth is stunted or dead. 5,16 This study was still in vitro tests; therefore, it did not reflect the real condition found in periodontal pockets. It did not consider the factors such as the interaction of host, agent, and environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to suhartati et al, (2019) Flavonoids can perform inhibition mechanism by interfering with the bacterial cell wall synthesis there by causing plasma leakage resulting in lysis of the bacteria . Inhibition occurs also (Suhartati 2019) et al there is a process of protein synthesis, inhibition of protein synthesis occurs where there is a process of transcription and translation of genetic material so that the amino acids produced incorrectly place themselves in the peptide chain and produce proteins that do not function . Flavonoid compounds (Madigan 2008) et al can damage cell walls, causing cell death (Haeria and Hermawati 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mangosteen rind, mangosteen leaves contain active compounds such as flavonoids, alkaloids, saponins, and tannins [ 13 ]. Some research results show that extracting mangosteen leaves can use ethanol [ 13 , 14 ] and methanol [ 15 ], but these solvents are not applicable and expensive when applied to the livestock sector. Information regarding the use of distilled water and extraction time to produce secondary metabolites is still limited.…”
Section: Introductionmentioning
confidence: 99%